Tradition of the forced marriage of couples who return late at night perspective of Islamic law: Case study of the tradition of the Lekuk Lima Puluh Tumbi Lempur Society, Jambi - Arzam; Mega Puspita; Zezen Zainul Ali; Zufriani; Mursal (IBDA` : Jurnal Kajian Islam dan Budaya, 2023)
Islam upholds the principle of willing consent in marriage, prohibiting coercion, yet in the Lekuk Lima Puluh Tumbi Lempur Jambi community, forced marriages occur due to local customs, leading to negative consequences. The research method used was field research focusing on the Lekuk Lima Puluh Tumbi Lempur community, Jambi, Indonesia. The data obtained were analyzed and studied with Islamic law. The findings first show that the forced marriage occurs when a man and a woman return to the village after a late night. Second, factors behind these customary sanctions include religious, social and customary ones. Third, the impact of these customary sanctions is the occurrence of underage marriage and the resultant divorce. Fourthly, the marriage is contrary to Islamic law, because it involves coercion, even though the pillars of marriage are fulfilled, but the conditions of marriage are not fulfilled, so the law of marriage becomes fasid (broken). Therefore, as a consideration, if the sanction of forced marriage is carried out without regard to the cause, whether chronological or consensual, and age, but only based on customary coercion, then the customary sanction can cause more significant harm than benefit, so the custom must be abandoned.